Epistemology & Methodology III: Philosophy of Science and Technology Part I: Formal and Physical Sciences - Bunge, M. author. aut Link
XI, 263 p.
Keywords: The aims of this Introduction are to characterize the philosophy of science and technology, henceforth PS & T, to locate it on the map ofiearning, and to propose criteria for evaluating work in this field. 1. THE CHASM BETWEEN S & T AND THE HUMANITIES It has become commonplace to note that contemporary culture is split into two unrelated fields: science and the rest, to deplore this split - and to do is some truth in the two cultures thesis, and even nothing about it. There greater truth in the statement that there are literally thousands of fields of knowledge, each of them cultivated by specialists who are in most cases indifferent to what happens in the other fields. But it is equally true that all fields of knowledge are united, though in some cases by weak links, forming the system of human knowledge. Because of these links, what advances, remains stagnant, or declines, is the entire system of S & T. Throughout this book we shall distinguish the main fields of scientific and technological knowledge while at the same time noting the links that unite them.